Variations of Arterial Supply to Adrenal Gland: Clinical Implications and Observations - K. Naga Vidya Lakshmi; Mahesh Dhoot (New Advances in Medicine and Medical Science Vol. 4, 2023)
This chapter highlights the variations in the arterial pattern of adrenal gland. Adrenal glands are a pair of endocrine glands located in relation to the upper poles of kidney which secretes hormones that are essential to human life. This study is performed in the Anatomy Department, RKDF Medical College, Hospital and Research Centre, Bhopal by symmetrically dissecting 15 formalin preserved cadavers to trace the arterial supply of the adrenal gland. Adrenal gland shows complexity in its blood supply and variability in the origin and the position of arteries supplying them. In the present work in one case on the right side IPA has come from the RA. At the junction of these two MSA was given off. One case on left showed the origin of MSA from CT. A surgeon must have a thorough understanding of the different adrenal gland vasculature in order to perform procedures like adrenalectomy, kidney transplants, and radiological arbitrations.